Neoclerodane diterpenoids from aerial parts of Scutellaria barbata. (March 2017) - Yang, Guo-Chun; Liang, Chen; Li, Sheng-Ge; Liu, Min; Jia, Ming-Jing; Xu, Xiao-Nan; Wang, Xiao-Bo; Hua, Hui-Ming; Sun, Li-Xin
Graphical abstract: Highlights: Three new neoclerodane diterpenoids were isolated from aerial parts of Scutellaria barbata . Absolute configurations of 1 and 2 were determined by CD exciton chirality and ECD calculation. Compounds 1–3 showed no in vitro cytotoxicity against three human cancer cell lines. Abstract: Three new neoclerodane diterpenoids, scutebatas U-W (1 –3 ), along with nine known ones (4 –12 ) were obtained via the phytochemical investigation of the aerial parts of Scutellaria barbata. The structure of these compounds was established by spectroscopic analysis. The absolute configurations of1 and2 were elucidated based on CD exciton chirality and electronic circular dichroism (ECD) calculation. Moreover, compounds1 -3 were evaluated for in vitro cytotoxicity against three human cancer cell lines (A549, MCF7 and SGC7901). However, compounds1 -3 were inactive against the three cell lines (IC50  > 100 μg/mL).